The Use of Social Media and Digital Devices Among Italian Neurologists - Lavorgna, Luigi; Brigo, Francesco; Abbadessa, Gianmarco; Bucello, Sebastiano; Clerico, Marinella; Cocco, Eleonora; Iodice, Rosa; Lanzillo, Roberta; Leocani, Letizia; Lerario, Alberto; Moccia, Marcello; Padovani, Alessandro; et al. (Frontiers in Neurology, 2020)
Background: Digital devices and online social networks are changing clinical practice. In this study we explored attitudes, awareness, opinions and experiences of neurologists towards social media and digital devices. Methods: Each member of the Italian Society of Neurology (SIN) participated to an online survey (January to May 2018) to collect information on their attitude towards digital health. Results: 405 Neurologists participated to the study. At work, 95% of responders use the personal computer, 87% the smartphone, and 43.5% the tablet. These devices are used to obtain health information (91%), maintain contact with colleagues (71%), provide clinical information (59%), and receive updates (67%). Most participants (56%) use social media to communicate with patients, although 65% are against a friendship with them on social media. Most participants interact with patients on social media outside working hours (65.2%) and think that social media have improved (38.0%) or greatly improved (25.4%) the relationship with patients. Most responders (66.7%) have no wearable devices available in clinical practice. Conclusion: Italian neurologists have different practices and views regarding the doctor-patient relationship in social media. The availability of digital devices in daily practice is limited. The use of social networks and digital devices will increasingly permeate into everyday life, bringing a new dimension to health care. The danger is that advancement will not go hand in hand with a legal and cultural adaptation, thus creating ambiguity and risks for clinicians and patients. Neurologists will need to be able to face the opportunities and challenges of this new scenario.